AGILE LEADERSHIP: A HYBRID SYSTEMATIC LITERATUREREVIEW AND BIBLIOMETRIC ANALYSIS - Sari Febrianti; Rahmi; Madhakomala; Hazrat Shah Kayen (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study aims to map the global research landscape on Agile Leadership through the analysis of articles indexed in Scopus. The analysis categorizes publications by country, institutional affiliation, source title, and primary author, while network visualization and keyword co-occurrence are examined using VOSviewer. This study is motivated by the growing need for adaptive leadership in response to rapid technological change, digital transformation, and post-pandemic challenges, as well as the fragmented nature of the Agile Leadership concept in the existing literature. A systematic literature review combined with bibliometric analysis, reviewing 64 articles indexed in the Scopus database published between 2005 and 2026 using the PRISMA framework and VOSviewer. The results indicate that Agile Leadership research has shown a significant upward trend since 2019, with a peak in 2024 based on VOSviewer results, reflecting increasing academic interest. Moreover, Agile Leadership is closely related to organizational agility, innovation, digital transformation, and human resource management, highlighting its multidimensional nature. However, this study identified several research gaps, including limited empirical evidence and underexplored areas such as employee well-being and cross-cultural contexts. In summary, Agile Leadership emerges as a multidimensional and evolving construct that plays a strategic role in addressing contemporary organizational challenges, while offering significant opportunities for future research across diverse contexts. Keywords: Agile Leadership; Bibliometric Analysis; Systematic Literature Review Abstrak Studi ini bertujuan untuk memetakan lanskap penelitian global tentang Kepemimpinan Agile melalui analisis artikel yang diindeks di Scopus. Analisis mengkategorikan publikasi berdasarkan negara, afiliasi institusional, judul sumber, dan penulis utama, sementara visualisasi jaringan dan kemunculan bersama kata kunci diperiksa menggunakan VOSviewer. Studi ini dimotivasi oleh meningkatnya kebutuhan akan kepemimpinan adaptif sebagai respons terhadap perubahan teknologi yang cepat, transformasi digital, dan tantangan pasca-pandemi, serta sifat fragmentasi konsep Kepemimpinan Agile dalam literatur yang ada. Tinjauan literatur sistematis yang dikombinasikan dengan analisis bibliometrik, meninjau 64 artikel yang diindeks dalam basis data Scopus yang diterbitkan antara tahun 2005 dan 2026 menggunakan kerangka kerja PRISMA dan VOSviewer. Hasil menunjukkan bahwa penelitian Kepemimpinan Agile telah menunjukkan tren peningkatan yang signifikan sejak tahun 2019, dengan puncaknya pada tahun 2024 berdasarkan hasil VOSviewer, yang mencerminkan peningkatan minat akademis. Selain itu, Kepemimpinan Agile terkait erat dengan ketangkasan organisasi, inovasi, transformasi digital, dan manajemen sumber daya manusia, yang menyoroti sifat multidimensionalnya. Namun, studi ini mengidentifikasi beberapa kesenjangan penelitian, termasuk bukti empiris yang terbatas dan area yang kurang dieksplorasi seperti kesejahteraan karyawan dan konteks lintas budaya. Singkatnya, Kepemimpinan Agile muncul sebagai konstruksi multidimensional dan berkembang yang memainkan peran strategis dalam mengatasi tantangan organisasi kontemporer, sekaligus menawarkan peluang signifikan untuk penelitian masa depan di berbagai konteks. Kata kunci: Kepemimpinan Tangkas; Tinjauan Literatur Sistematis; Analisis Bibliometrik.